PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAMS GAME TOURNAMENT (TGT) BERBANTUAN MEDIA INTERAKTIF SMARTGAPOLY TERHADAP PRESTASI BELAJAR AKUNTANSI DITINJAU DARI KECERDASAN EMOSI SISWA SMK - Satiti, Abidah Dwi Rahmi; Suhardjanto, Djoko; Susilaningsih, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2016)
The objective of this research was to investigate the difference effect between the TGT cooperative learning model assisted Smartgapoly interactive media (MPK-TGT Smartgapoly) and the direct learning model (MPL) on learning achievement in Accounting viewed emotional intelligence. This research was an quasi experimental with nonequivalent pretest and posttest control-group design. The population of research was the students in Grade X of Business and Management Department, State Vocational High School 1 Karanganyar as many as 7 classes. The samples of research consisted of 2 classes. The data were analyzed by using the two-way analysis of variance and was continued with the Scheffe test. The findings showed that: (1) there was a difference effect between MPK-TGT Smartgapoly and MPL on learning achievement in Accounting; (2) there was a difference effect of the high, moderate, and low emotional intelligence on learning achievement in Accounting; and (3) there was an interaction between MPK-TGT Smartgapoly and MPL with emotional intelligence on learning achievement in Accounting. Keywords: Teams Game Tournament, direct learning, Smartgapoly, learning achievement in Accounting, emotional intelligence